2008
DOI: 10.1681/asn.2007050580
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-to-Mesenchymal Transition in Early Transplant Tubulointerstitial Damage

Abstract: It is unknown whether epithelial-to-mesenchymal transition (EMT) leads to tubulointerstitial fibrosis in renal transplants. In this study, interstitial fibrosis and markers of EMT were followed in protocol transplant biopsies in 24 patients. Tubulointerstitial damage (TID) increased from 34 to 54% between 1 and 3 mo after transplantation. Detection of EMT depended on the marker used; low levels of ␣-smooth muscle actin were found in 61% of biopsies, but the less specific marker S100 calcium binding protein-A4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 44 publications
0
20
1
Order By: Relevance
“…Caution is advised in interpreting these data, however, because recent studies have challenged the existence of this epithelial-mesenchymal transition in kidney disease. 45 In opposition to our predictions, and despite the fact that inflammatory reactions after VEGF-stimulation are thought to be attributed to VEGFR1, not VEGFR2, 11,12 selective VEGFR2 stimulation elevated macrophage infiltration as assessed by F4/80 and CD68 staining, regardless of eNOS expression, The renal macrophage infiltration observed in the present study was unlikely to be due to direct VEGFR2 stimulation, but probably was due to an indirect effect from other cytokines that may be expressed in injured kidneys.…”
Section: Discussioncontrasting
confidence: 99%
“…Caution is advised in interpreting these data, however, because recent studies have challenged the existence of this epithelial-mesenchymal transition in kidney disease. 45 In opposition to our predictions, and despite the fact that inflammatory reactions after VEGF-stimulation are thought to be attributed to VEGFR1, not VEGFR2, 11,12 selective VEGFR2 stimulation elevated macrophage infiltration as assessed by F4/80 and CD68 staining, regardless of eNOS expression, The renal macrophage infiltration observed in the present study was unlikely to be due to direct VEGFR2 stimulation, but probably was due to an indirect effect from other cytokines that may be expressed in injured kidneys.…”
Section: Discussioncontrasting
confidence: 99%
“…In most cell types investigated, CTGF was upregulated, e.g., endothelial (25) and chondrosarcoma cells (24). Inconsistently, hypoxic upregulation of CTGF was observed in human breast cancer cell line MDA-231 (26,40), whereas a lack of change was reported in MCF-7 human breast cancer cells (10). Upregulation was also described in murine tubular epithelial cells (17), which is in contrast to downregulation of CTGF observed in human tubular cell lines (26), or in primary cell cultures analyzed by gene expression microarray (7).…”
Section: Discussionmentioning
confidence: 94%
“…This suggested that CTGF might play a role in mesenchymal transition of tubular epithelial cells, which is considered to play a role in progressive kidney disease (5). However, markers of mesenchymal transition did not correlate with interstitial fibrosis, as analyzed in protocol transplant biopsies (40). While the concept of mesenchymal transition is well established in tumor cells or mouse models, the extent to which it contributes to human renal tubulointerstitial fibrosis is under debate (e.g.,…”
mentioning
confidence: 99%
“…226 Glis2 mutations producing autosomal recessive NPHP7, a rare form of nephronophthisis, may be the first suggestive evidence of spontaneous or derepressed EMT causing renal fibrosis in humans. 212,227 EMT induces a variety of intermediate cell phenotypes, not all of which complete their transition to fibroblasts.…”
Section: Fibroblastsmentioning
confidence: 99%